Optimalisasi Penggunaan LKPD Untuk Meningkatkan Keterampilan Proses Komunikasi Jenis Visual - Annisa Damayanti; Rizki Hadiwijaya Z; Winarti Dwi Febriani (Universitas 45 Surabaya, 2024)
The background to this research is the low level of optimization of the use of LKPD in science learning in class IV of SDN Pahlawan, Tasikmalaya City. This research aims to determine and analyze the planning, implementation and improvement of students' visual skills in optimizing LKPD in science learning with magnetic magnetic material. The method used in this research is Classroom Action Research (PTK) according to the Kemmis and Mc model. Taggart which consists of planning, action, observation and reflection in each cycle. The discussion of this research uses LKPD in the learning process and tests are carried out at the end of each cycle. The research results stated that the results of optimizing learning using LKPD in class IV SDN 1 Pahlawan Tasikmalya City were able to increase the optimization of students' visual communication. This increase after using the LKPD in cycle I obtained an average value of 2.31 with a percentage of 32.46% in the